The Power in Stories That Cannot Be Replaced - Chrismas, Robert W, PhD (NSUWorks, 2018)
This paper is based upon research that included interviews with 61 experts across Manitoba, including police, First Nations and other political leaders, government and non-government service providers and sex trafficking survivors, who collectively represent over 1,000 years of experience combatting victimization in the sex industry. It describes a researcher’s experience taking a qualitative, story-based approach to investigating the modern social problem of sex-trafficking. Based on his thesis, “Modern Day Slavery and the Sex Industry: Raising the Voices of Survivors and Collaborators While Confronting Sex Trafficking and Exploitation in Manitoba” the author highlights the power that the stories hold, emphasizing how no other method of research would be quite as effective. The power of the stories told simply cannot be replaced.